Assessing the potential for “assisted gene flow” to enhance heat tolerance of multiple coral genera over three key phenotypic traits - Macadam, Alex; Morgans, Carys; Cheok, Jessica; Damjanovic, Katarina; Ciampaglia, Melissa; Toor, Maren; Laffy, Patrick; Cooke, Ira R.; Strugnell, Jan M.; Quigley, Kate M. (Biological conservation, 2025)
Mass coral bleaching and mortality events have increased in frequency over the last 30 years, with ocean temperatures projected to reach bleaching thresholds annually by 2050. Genetic interventions like assisted gene flow may speed up adaptation in reefs with less heat-tolerant corals by increasing the frequency of heat tolerance-associated genetic variants, but the effectiveness of the intervention across species and life stages remains uncertain. To investigate, we generated reproductive crosses of corals from reefs along a thermal gradient on the Great Barrier Reef, comparing fitness traits in intra-region (same region) and inter-region (different region) offspring from three species (Acropora kenti, A. hyacinthus, and Goniastrea retiformis). Juveniles were inoculated with three heat-tolerant symbionts: Durusdinium trenchii, a heat-evolved Cladocopium goreaui strain, and “wild” symbionts from northern reef sediments, to assess symbiosis impacts on heat tolerance. Survival, growth, colour change (proxy for bleaching), and effective quantum yield of photosystem II (YII) were measured across larvae, juveniles, and adults at elevated (32 °C, 35.5 °C) and ambient (27.5 °C) temperatures. Results showed higher survival in some inter-region crosses compared to intra-region crosses from central reefs in larvae and juvenile corals, though enhancement varied by species. Furthermore, heat-tolerant parents did not always produce heat-tolerant offspring, and larval heat tolerance did not always persist to the juvenile stage. Parent genetic background influenced survival more than symbiont treatment. These findings underscore the complexity of heat tolerance acquisition in early coral life stages.